Hubungan Antara Efektivitas Fungsi Bimbingan dan Konseling Dengan Persepsi Siswa Terhadap Bimbingan dan Konseling di Sekolah Menengah Pertama Stella Duce I Yogyakarta - Batuadji, Kristianto; Atamimi, Nuryati; Sanmustari, Rasimin B. (Jurnal Psikologi, 2009)
The aim of this istudy is to investigate the relationship between the effectiveness of guidance and counsellingâ€™s function and studentâ€™s perception towards guidance and counselling in Stella Duce I Middle School of Yogyakarta. It was hypothesized that there is a positive relationship between effectiveness of guidance and counsellingâ€™s function and studentâ€™s perception towards guidance and counselling. The subjects of this study (N = 117) were the students of Stella Duce I Middle School of Yogyakarta. Two questionnaires were applied to measure effectiveness of guidance and counsellingâ€™s function and studentâ€™s perception towards guidance and counselling. The result indicated a positive and significant relationship between effectiveness of guidance and counsellingâ€™s function and studentâ€™s perception towards guidance and counselling (r = 0,677 p = 0,000), meaning that the research hypothesis was accepted. The determination coefficient was 0,459 indicating that the effectiveness of guidance and counsellingâ€™s function contributes 45, 9% to the development of studentâ€™s perception towards guidance and counâ€selling.